Matrix‐Gla protein promotes osteosarcoma lung metastasis and associates with poor prognosis. Issue 4 (29th June 2016) - Zandueta, Carolina; Ormazábal, Cristina; Perurena, Naiara; Martínez‐Canarias, Susana; Zalacaín, Marta; Julián, Mikel San; Grigoriadis, Agamemnon E; Valencia, Karmele; Campos‐Laborie, Francisco J; Rivas, Javier De Las; Vicent, Silvestre; Patiño‐García, Ana; et al.
Abstract: Osteosarcoma (OS) is the most prevalent osseous tumour in children and adolescents and, within this, lung metastases remain one of the factors associated with a dismal prognosis. At present, the genetic determinants driving pulmonary metastasis are poorly understood. We adopted a novel strategy using robust filtering analysis of transcriptomic profiling in tumour osteoblastic cell populations derived from human chemo‐naive primary tumours displaying extreme phenotypes (indolent versus metastatic) to uncover predictors associated with metastasis and poor survival. We identified MGP, encoding matrix‐Gla protein (MGP), a non‐collagenous matrix protein previously associated with the inhibition of arterial calcification. Using different orthotopic models, we found that ectopic expression of Mgp in murine and human OS cells led to a marked increase in lung metastasis. This effect was independent of the carboxylation of glutamic acid residues required for its physiological role. Abrogation of Mgp prevented lung metastatic activity, an effect that was rescued by forced expression. Mgp levels dramatically altered endothelial adhesion, trans‐endothelial migration in vitro and tumour cell extravasation ability in vivo . Furthermore, Mgp modulated metalloproteinase activities and TGFβ‐induced Smad2/3 phosphorylation. In the clinical setting, OS patients who developed lung metastases had high serum levels of MGP at diagnosis. Thus, MGP represents a novel adverse prognostic factor and a potential therapeutic target in OS. Microarray datasets may be found at:http://bioinfow.dep.usal.es/osteosarcoma/ Copyright © 2016 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.